Neonatal Mortality in Two Tertiary Pediatric Hospitals in Baghdad (2012-2016) - Jawad, Hasanein A.; Al-kaseer, Eman A.; Al-Diwan, Jawad KA (Journal of the Faculty of Medicine Baghdad, 2018)
number of neonatal mortality rate (NMR). This study was conducted to clarify the relationship between conflict and neonatal mortality in Baghdad, Iraq. Objective: Throw a light on the impact of conflicts on neonatal mortality in Iraq. Methods: This cross-sectional study was carried out in two hospitals in Baghdad that were chosen randomly. All deceased newborns in neonatal intensive care units from January 2012 to December 2016 in the mentioned hospitals were included in this study. Results: The admissions were increased during the period of the study by 1.3 times. There was a decrease in admission by 0.9 in 2016 than 2015. There was an increase in NMR during the period of the study by 1.4 times, from 60/1000 in 2012 to 85/1000 in 2016. Conclusions: There has been an observed increase in neonatal mortality in Iraq due to the impact of conflicts that have led to deterioration in the neonatal health status. الخلفية: ربطت تقارير عديدة بين انتشار العنف والنزاعات المسلحة وزيادة معدلات وفيات حديثي الولادة. اجريت هذه الدراسة لتوضيح العلاقة بين النزاعات ووفيات الاطفال حديثي الولادة في بغداد، العراق. الاهداف: بيان مدى تأثير النزاعات على وفيات الأطفال حديثي الولادة في بغداد، العراق. الطرائق: أجريت هذه الدراسة المقطعية في مستشفيين في بغداد تم اختيار بشكل عشوائي. وقد شملت هذه الدراسة جميع المواليد حديثي الولادة في وحدات العناية المركزة لحديثي الولادة من كانون الثاني / يناير 2012 إلى كانون الأول / ديسمبر 2016 في المستشفيات المذكورة. النتائج: ازداد ادخال المواليد الجدد الى العناية المركزة بمقدار ١٫٣ مرة خلال فترة الدراسة. قل ادخال المواليد بمقدار ٠٫٩ في ٢٠١٦ عن السنة السابقة. نسبة وفيات المواليد الجدد ازدادت بمقدار ١٫٤ مرة خلال فترة الدراسة. نسبة وفيات المواليد الجدد كانت ٦٠ لكل ١٠٠٠ ولادة حية في العام ٢٠١٢ وأصبحت ٨٥ لكل ١٠٠٠ ولادة حية في العام ٢٠١٦. الاستنتاج: حدثت زيادة ملحوظة في وفيات المواليد الجدد في العراق بسبب تأثير النزاعات التي أدت إلى تدهور الوضع الصحي لحديثي الولادة.